Deletion of a hybrid NRPS‐T1PKS biosynthetic gene cluster via Latour gene knockout system in Saccharopolyspora pogona and its effect on butenyl‐spinosyn biosynthesis and growth development. Issue 6 (31st October 2020) - Rang, Jie; Li, Yunlong; Cao, Li; Shuai, Ling; Liu, Yang; He, Haocheng; Wan, Qianqian; Luo, Yuewen; Yu, Ziquan; Zhang, Youming; Sun, Yunjun; Ding, Xuezhi; et al.
Summary: Butenyl‐spinosyn, a promising biopesticide produced by Saccharopolyspora pogona, exhibits stronger insecticidal activity and a broader pesticidal spectrum. However, its titre in the wild‐type S. pogona strain is too low to meet the industrial production requirements. Deletion of non‐target natural product biosynthetic gene clusters resident in the genome of S. pogona could reduce the consumption of synthetic precursors, thereby promoting the biosynthesis of butenyl‐spinosyn. However, it has always been a challenge for scientists to genetically engineer S. pogona . In this study, the Latour gene knockout system (linear DNA fragment recombineering system) was established in S. pogona . Using the Latour system, a hybrid NRPS‐T1PKS cluster (˜20 kb) which was responsible for phthoxazolin biosynthesis was efficiently deleted in S. pogona . The resultant mutant S. pogona ‐Δ ura4‐ Δc14 exhibited an extended logarithmic phase, increased biomass and a lower glucose consumption rate. Importantly, the production of butenyl‐spinosyn in S. pogona ‐Δ ura4‐ Δc14 was increased by 4.72‐fold compared with that in the wild‐type strain. qRT‐PCR analysis revealed that phthoxazolin biosynthetic gene cluster deletion could promote the expression of the butenyl‐spinosyn biosynthetic gene cluster. Furthermore, a TetR family transcriptional regulatory gene that could regulate the butenyl‐spinosyn biosynthesis has been identified from the phthoxazolin biosynthetic gene cluster. Because dozens of natural product biosynthetic gene clusters exist in the genome of S. pogona, the strategy reported here will be used to further promote the production of butenyl‐spinosyn by deleting other secondary metabolite synthetic gene clusters. Abstract : Using the Latour system, a hybrid NRPS‐T1PKS cluster (˜20 kb) which was responsible for phthoxazolin biosynthesis was efficiently deleted in S. pogona . A TetR family transcriptional regulatory gene that could regulate the butenyl‐spinosyn biosynthesis has been identified from the phthoxazolin biosynthetic gene cluster.